Prevalence of transient congenital hypothyroidism in central part of Iran - Ghasemi, Mahmoud (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Congenital hypothyroidism (CH) considered a common endocrine disorder in Iran. We report the epidemiologic findings of CH screening program in Isfahan, seven years after its development, regarding the prevalence of transient CH (TCH) and its screening properties comparing with permanent CH (PCH). MATERIALS AND METHODS: In this cross-sectional study, children with primary diagnosis of CH were studied. Considering screening and follow-up lab data and the decision of pediatric endocrinologists, the final diagnosis of TCH was determined. RESULTS: A total of 464,648 neonates were screened. The coverage percent of the CH screening and recall rate was 98.9 and 2.1%, respectively. Out of which, 1,990 neonates were diagnosed with primary CH. TCH was diagnosed in 1,580 neonates. The prevalence of TCH was 1 in 294 live births. 79.4% of patients with primary CH had TCH. Mean of screening (54.7 ± 59.0 in PCH vs 21.8 ± 28.9 in TCH), recall (56.5 ± 58.8 in PCH vs 36.6 ± 45.0 in TCH), and thyroid stimulating hormone (TSH) and mean of TSH before (2.0 ± 2.9 in PCH vs 1.6 ± 1.6 in TCH) and after (37.7 ± 29.5 in PCH vs 4.3 ± 1.9 in TCH) discontinuing treatment at 3 years of age was significantly higher in PCH than TCH (P < 0.0000). CONCLUSION: The higher rate of CH in Isfahan is mainly due to the transient form of the disease. Further studies for evaluating the role of other environmental, autoimmune and/or genetic factors in the pathophysiology of the disease is warranted.